Diagnostic Analysis of Eleventh-Grade Students' Errors in Solving Quadratic Function Problems Based on Newman's Error Analysis - Kholifatul Aulia; Rikayanti; Muhammad Daut Siagian (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to describe the characteristics and types of errors made by eleventh-grade high school students, along with their percentages of occurrence at each stage of Newman's Error Analysis (NEA), when solving quadratic function problems. A descriptive qualitative method supported by percentage analysis of student errors was employed. The research subjects consisted of 30 eleventh-grade high school students selected using purposive sampling. Data were collected through a validated open-ended diagnostic test and analyzed using the Miles and Huberman model. The analysis results show that errors occurred at all stages of the NEA, with the following average percentage distributions: reading errors at 4.7%, comprehension errors at 66.7%, transformation errors at 63.3%, process skill errors at 73.3%, and Encoding errors at 78.0%. Reading errors had the lowest frequency, while students' main difficulties were observed at the process-skills and final-answer-writing stages, particularly in contextual problems and algebraic manipulation involving fractions. Students' errors were systematic and hierarchical, with deficiencies at the transformation and process-skills stages as the dominant factors contributing to students' failure to produce accurate final answers. The findings recommend strengthening students' conceptual understanding of the vertex, factoring of quadratic functions, and basic procedural algebra skills in classroom instruction.